Plutarch's Religious Landscapes - Hirsch-Luipold, Rainer,; Lanzillotta, Lautaro Roig, (Brill's Plutarch Studies ;, 2021)
A Platonist philosopher and priest of Apollo at Delphi, Plutarch (ca. 45-120 CE) covers in his vast oeuvre of miscellaneous writings and biographies of great men virtually every aspect of ancient religion, Greek, Roman, Jewish, Egyptian, Persian. This collection of essays takes the reader on a hike through Plutarch's Religious Landscapes offering as a compass the philosopher's considerations on issues of philosophical theology, cult, ethics, politics, natural sciences, hermeneutics, atheism, and life after death. Plutarch provides a unique vantage point to reconstruct and understand many of the interesting developments that were taking in the philosophical and religious world of the first centuries CE.